The adverse effects of reduced cerebral perfusion on cognition and brain structure in older adults with cardiovascular disease. Issue 6 (10th September 2013) - Alosco, Michael L.; Gunstad, John; Jerskey, Beth A.; Xu, Xiaomeng; Clark, Uraina S.; Hassenstab, Jason; Cote, Denise M.; Walsh, Edward G.; Labbe, Donald R.; Hoge, Richard; Cohen, Ronald A.; Sweet, Lawrence H.
Abstract Background It is well established that aging and vascular processes interact to disrupt cerebral hemodynamics in older adults. However, the independent effects of cerebral perfusion on neurocognitive function among older adults remain poorly understood. We examined the associations among cerebral perfusion, cognitive function, and brain structure in older adults with varying degrees of vascular disease using perfusion magnetic resonance imaging (MRI) arterial spin labeling (ASL). Materials and methods 52 older adults underwent neuroimaging and were administered the Mini Mental State Examination (MMSE), the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), and measures of attention/executive function. ASL and T1‐weighted MRI were used to quantify total brain perfusion, total brain volume (TBV), and cortical thickness. Results Regression analyses showed reduced total brain perfusion was associated with poorer performance on the MMSE, RBANS total index, immediate and delayed memory composites, and Trail Making Test B. Reduced frontal lobe perfusion was associated with worse executive and memory function. A similar pattern emerged between temporal lobe perfusion and immediate memory. Regression analyses revealed that decreased total brain perfusion was associated with smaller TBV and mean cortical thickness. Regional effects of reduced total cerebral perfusion were found on temporal and parietal lobe volumes and frontal and temporal cortical thickness. Discussion Reduced cerebral perfusion is independently associated with poorer cognition, smaller TBV, and reduced cortical thickness in older adults. Conclusion Prospective studies are needed to clarify patterns of cognitive decline and brain atrophy associated with cerebral hypoperfusion.